Born again evangelicalism in Korea - Lee, Timothy S. (Honolulu : University of Hawaii Press, 2010)
"Born Again" is the first book in a Western language to consider the introduction, development, and character of evangelicalism in Korea - from its humble beginnings at the end of the nineteenth century to claiming one out of every five South Koreans as an adherent at the end of the twentieth. --from publisher description
Breakthrough for a new moral order, 1885-1919 -- Conflict, introversion, and a tradition of Korean revivalists, 1920-1953 -- Evangelicalism takes off in South Korea, 1953-1988 -- The intensely practical and devotional character of Korean Evangelicalism -- The beleaguered success of Korean Evangelicalism in th 1990s.
Includes bibliographical references (p. 199-220) and index.
Description based on print version record.
Keywords: Evangelicalism -- Korea (South) -- History; Protestantism -- Korea (South); Korea (South) -- Church history -- 20th century; Presbyterianische Kirche in Korea; Geschichte; Evangelikale Bewegung; Protestantismus; Korea; Südkorea; Electronic books